NaMgH3 a perovskite-type hydride as advanced hydrogen storage systems: Electronic structure features. (14th December 2015) - Reshak, A.H.
Abstract: The physical properties of perovskite NaMgH3 has been comprehensively investigated by means of density functional theory. Calculations reveals that NaMgH3 is a wide band gap insulator. The angular momentum projected density of states and the valence electronic charge density explore that the NaMgH3 has high gravimetric and volumetric H densities. The calculated angular momentum projected density of states reveals that the hydrogen posses the highest density among Mg and Na. It has been found that a charge transfer occurs towards H atom. Complex first-order linear optical properties helps to further understand the physical properties of NaMgH3 . Analyzing the optical properties reveals the NaMgH3 posses negative uniaxial anisotropy and the optical properties give deep insight into the electronic structure. Highlights: The physical properties of perovskite NaMgH3 has been comprehensively investigated. NaMgH3 is a wide band gap insulator. NaMgH3 has high gravimetric and volumetric H densities. It has been found that a charge transfer occurs towards H atom.